Isoorientin Ameliorates APAP-Induced Hepatotoxicity via Activation Nrf2 Antioxidative Pathway: The Involvement of AMPK/Akt/GSK3β - Fan, Xiaoye; Lv, Hongming; Wang, Lidong; Deng, Xuming; Ci, Xinxin (Frontiers in Pharmacology, 2018)
Oxidative stress has been highlighted as therapeutic targets for acetaminophen (APAP)-induced hepatotoxicity. Isoorientin (ISO), the most important flavonoid-like compound, has been shown to have antioxidant potential. However, the effect of isoorientin on APAP-induced liver injury has not yet been elucidated. The present study investigated the hepatoprotective effect and mechanism of isoorientin. C57BL/6J mice were used to evaluate the hepatoprotective effect of isoorientin in vivo and HepG2 cells were utilized to further decipher the mechanisms of isoorientin -induced Nrf2 activation. We found that isoorientin treatment significantly reduced APAP-induced hepatotoxicity by alleviating the lethality, histopathological liver changes, alanine transaminase (ALT) and aspartate aminotransferase (AST) levels in serum. These were accompanied by decreasing malondialdehyde (MDA) formation, myeloperoxidase level (MPO), and superoxide dismutase (SOD) and glutathione (GSH) depletion. Moreover, isoorientin induced Nrf2 activation and translocation, as well as its upstream AMPK/Akt/GSK3β activation. Furthermore, isoorientin efficiently alleviated mitochondrial dysfunction by reducing c-jun N-terminal kinase phosphorylation and translocation, Bax mitochondrial translocation, as well as apoptosis-inducing factor and cytochrome c release. Further mechanistic investigations reveal that activation of Nrf2 via the AMPK/Akt/GSK3β pathway a by isoorientin contribute to its hepatoprotetive activity in vitro. In addition, isoorientin-inhibited APAP-induced the lethality, histopathological changes and mitochondrial dysfunction in WT mice were almost abolished in Nrf2 -/- mice. In summary, isoorientin ameliorate APAP-induced hepatotoxicity by activating Nrf2 via AMPK/Akt/GSK3β pathway.